Kingship and memory in ancient Judah - Wilson, Ian Douglas 1981- (Oxford Oxford University Press USA - OSO, 2017)
Kingship and Memory in Ancient Judah investigates kingship in Judean discourse, particularly in the early Second Temple era. In doing so, it contributes to our knowledge of literature and literary culture in ancient Judah and also makes a significant contribution to questions of history and historiographical method in biblical studies.
Cover -- Kingship and Memory in Ancient Judah -- Copyright -- Dedication -- Contents -- Acknowledgments -- List of Abbreviations -- 1. Ancient Judah and Its Literature: Remembering and Imagining Kingship -- Judean Literature and Its Sociocultural Setting -- Judean Literati of the Early Second Temple Era -- Kingship Discourse among the Literati -- Memory, Remembering, Imagining: Past, Present, and Future in Society and Culture -- Social Memory and Narrativity: A Good Working Relationship -- Moving Forward -- 2. Torah and Its Guardians -- The Law of the King's Deuteronomic Setting -- The Law of the King and Its Interlocutors -- Moses and Joshua, Kings and Conquerors: Revising Monarchy in a Postmonarchic Milieu -- The Law of the King as a Mnemonic Frame -- 3. Cruxes of Leadership: The Transition(s) to Monarchy -- Setting Up Samuel -- The Trouble with Transitions -- Gideon and Abimelech: Serious Family Issues -- The Aporia of Samuel, Dynasty, and Divine Promises -- Yahweh, Samuel, Saul: Rivalries of Political Identification in 1 Sam 8-12 -- Outcomes of Rivalry and Aporia: Kingship's Beginnings in Israel -- To the Heart of the Issue -- 4. Remembering/Forgetting David and Davidic Kingship -- David as Character, Plot, Narrative in Samuel-Kings and Judah's Social Memory -- Chronicles and Samuel-Kings: Both among the Literati -- And the Rest of the Story? The Potentials and Outcomes of Davidic Kingship in Solomon's Narrative -- On Book Endings, Davidic Kingship, and Judean Metanarratives -- 5. The Remembered Future in Prophetic Literature -- From Prophets and Prophecy to the Prophetic Book -- King Yahweh -- The Hedging of David -- King Israel -- Historical Consciousness, Metahistory, and the Prophetic Book -- 6. To Conclude: The Emplotments of Kingship and "Metahistoriography" in Ancient Judah -- The Rhyming of Kingship: An Outline.
Description based on publisher supplied metadata and other sources
Keywords: Kings and rulers--Bible teaching; Electronic books; Bible; Jews; Kings and rulers; Memory; Hochschulschrift